Composite negative electrode material and preparation method thereof, negative electrode sheet, secondary battery and electric device

By using composite negative electrode materials in lithium-ion batteries, the problems of low conductivity and cycle life caused by silicon-based materials are solved, higher conductivity and cycle life are achieved, and the overall performance of the battery is improved.

CN116093273BActive Publication Date: 2025-02-25CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211374915.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-04
Publication Date
2025-02-25
Estimated Expiration
2042-11-04

AI Technical Summary

Technical Problem

The silicon-based materials used in existing lithium-ion batteries lead to low conductivity and cycle life, which cannot meet actual use needs.

Method used

A composite negative electrode material is used, which includes a silicon-based material matrix and a polymer structure covered with a surface of the silicon-based material matrix. The polymer structure consists of an organic polymer and a hydroxylated carbon nanotube, and some organic polymers are formed by combining with hydroxylated CNTs. The composite is connected to the silicon-based material matrix through an ester group and a hydrogen bond.

Benefits of technology

It improves the conductivity and cycle life of the secondary battery, reduces the rebound of the electrode sheet, enhances the processability of the battery cell, and effectively protects the surface of the silicon-based material, extends the cycle life of the battery cell.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116093273B_ABST
    Figure CN116093273B_ABST
Patent Text Reader

Abstract

The present application provides a composite negative electrode material and a preparation method thereof, a negative electrode plate, a secondary battery and an electrical device, wherein the composite negative electrode material comprises: a silicon-based material matrix and a polymer structure coated on at least part of the surface of the silicon-based material matrix, wherein the polymer structure comprises an organic polymer and hydroxylated carbon nanotubes, at least part of the organic polymer is combined with the hydroxylated carbon nanotubes to form a composite, and the organic polymer comprises a compound having a structure shown in formula (1), wherein m is an integer of 2500 to 20000, and R1 is a polymer unit containing an ester group and a nitrile group. The composite negative electrode material provided by the present application can improve the conductivity and cycle life of the secondary battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of electrochemical technology, and in particular relates to a composite negative electrode material and a preparation method thereof, a negative electrode sheet, a secondary battery and an electrical device. Background Art

[0002] In recent years, the application scope of secondary batteries represented by lithium-ion batteries has become increasingly wide. Secondary batteries are widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields. As secondary batteries have made great progress, higher requirements have been put forward for their energy density, cycle performance and safety performance. At present, in secondary batteries represented by lithium-ion batteries, silicon-based materials are widely used due to their high capacity, but the use of silicon-based materials generally leads to low conductivity and cycle life of secondary batteries, which cannot meet actual usage needs. Summary of the invention

[0003] The purpose of the present application is to provide a composite negative electrode material and a preparation method thereof, a negative electrode plate, a secondary battery and an electrical device, which can improve the conductivity and cycle life of the secondary battery.

[0004] In order to achieve the above-mentioned invention object, the first aspect of the present application provides a composite negative electrode material, comprising: a silicon-based material substrate; and a polymer structure coated and connected to at least a portion of the surface of the silicon-based material substrate, wherein the polymer structure comprises an organic polymer and hydroxylated carbon nanotubes, at least a portion of the organic polymer is combined with the hydroxylated carbon nanotubes to form a composite, and the organic polymer comprises a compound having a structure shown in formula (1),

[0005]

[0006] In the formula (1), m is an integer of 2500 to 20000, and R1 is a polymerized unit containing an ester group and a nitrile group.

[0007] In the present application, the composite negative electrode material includes a silicon-based material matrix and a polymer structure connected to the surface of the silicon-based material matrix, wherein the organic polymer in the polymer structure and the hydroxylated CNT can fully realize linear polymerization to form a composite, and the composite can give full play to the coating effect of linear polymerization, and play a good inhibitory and restraining role on the volume expansion of the silicon-based material, thereby reducing the rebound of the pole piece and improving the cycle life of the battery cell. At the same time, the hydroxylated CNT in the polymer structure can also make up for the resistance deterioration caused by the coating and improve the conductivity of the composite negative electrode material. In addition, after the surface of the silicon-based material matrix is ​​coated and connected to the polymer structure, the contact area between the silicon-based material and the electrolyte can be reduced, the corrosion of the electrolyte to the silicon-based material can be reduced, and the surface of the silicon-based material can be effectively protected, thereby improving the performance of the silicon-based material during the cycle or storage process, and further improving the cycle life of the battery cell.

[0008] In some embodiments of the present application, the polymer unit includes a polymer unit of the structural formula shown in formula (2),

[0009]

[0010] In formula (2), ** represents the connection site of the polymer unit, p is an integer from 1000 to 5000, q is an integer from 1000 to 15000, f is an integer from 500 to 4000, 2≤n≤200, each R2 is independently selected from and One of the following, * indicates the connection site of R2, M + Selected from Na + , K + , Li + and NH4 + One of them.

[0011] Compared with traditional single-type monomer linear polymers, in the composite negative electrode material of the present application, the linear structure of the molecular chain contained in the polymerization unit contains more side chains composed of multiple different functional groups. These side chains can reduce the brittleness of the composite negative electrode material and enhance its flexibility, thereby enhancing the flexibility of the electrode piece; thus, after high compaction density cold pressing, the ductility of the electrode piece can be improved, which can effectively reduce the occurrence of edge overpressure; at the same time, it can also improve the phenomenon that the electrode piece under high compaction density is prone to brittle fracture in subsequent processing, thereby improving the processability of the electrode piece.

[0012] In some embodiments of the present application, the polymer structure is connected to at least a portion of the surface of the silicon-based material matrix through ester groups and / or hydrogen bonds; optionally, the hydroxylated carbon nanotubes are connected to at least a portion of the surface of the silicon-based material matrix through ester groups.

[0013] The polymer structure is connected to at least part of the surface of the silicon-based material matrix through the ester group, which can make the polymer bond on the surface of the composite negative electrode material not easy to fall off, thereby enhancing the firmness of the polymer structure's coating connection to the silicon-based material, so as to better exert the polymer structure's inhibitory and restraining effect on the volume expansion of the silicon-based material.

[0014] In some embodiments of the present application, the composite negative electrode material satisfies at least one of the following conditions:

[0015] (1) the silicon-based material matrix contains hydroxyl functional groups and / or carboxyl functional groups; and

[0016] (2) the organic polymer in the composite is combined with the hydroxylated carbon nanotube via an ester group and / or a hydrogen bond. Optionally, the organic polymer in the composite is combined with the hydroxylated carbon nanotube via an ester group;

[0017] (3) The surface of the hydroxylated carbon nanotube is connected with at least one hydroxyl group.

[0018] After the ester groups are formed between the hydroxylated carbon nanotubes and the organic polymers, the carboxyl functional groups in the organic polymers can be reduced, thereby reducing the hydrogen bonding effect between the molecules on the long polymer chains, effectively reducing the mutual agglomeration between the long polymer chains, improving the dispersion uniformity of the composite negative electrode material in the slurry, reducing the electrode sheet resistance, and thus improving the dynamic performance of the battery cell.

[0019] In some embodiments of the present application, the composite negative electrode material satisfies at least one of the following conditions:

[0020] (1) The silicon-based material includes at least one of elemental silicon, silicon-oxygen compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys; and

[0021] (2) The hydroxylated carbon nanotubes include hydroxylated single-walled carbon nanotubes and / or hydroxylated multi-walled carbon nanotubes.

[0022] The silicon-based material in the present application is a modified silicon-based material with hydroxyl groups and / or carboxyl groups grafted on the surface of the silicon-based material, and the hydroxylated carbon nanotube is a carbon nanotube with hydroxyl groups grafted on the surface of the carbon nanotube.

[0023] In some embodiments of the present application, the composite negative electrode material satisfies at least one of the following conditions:

[0024] (1) In the composite negative electrode material, the mass percentage of the silicon-based material matrix is ​​15% to 90%, and can be optionally 40% to 85%;

[0025] (2) In the composite negative electrode material, the mass percentage of the organic polymer is 6% to 60%, and can be optionally 15% to 25%;

[0026] (3) In the composite negative electrode material, the mass percentage of the composite is 10% to 80%, and can be optionally 20% to 50%.

[0027] The mass percentage of the silicon-based material matrix in the composite negative electrode material is within an appropriate range, which can ensure that the polymer structure has a good coating and connection effect on the silicon-based material matrix, thereby effectively inhibiting the volume expansion of the silicon-based material; and can also ensure that the composite negative electrode material has a high capacity. The mass percentage of the organic polymer in the composite negative electrode material is within an appropriate range, which can provide sufficient linear polymer structure for the formation of the composite in the polymer structure, ensure the full play of the performance of the organic polymer, improve the cycle life of the battery cell and the processability of the pole piece; and can also ensure that the composite negative electrode material has a high conductivity.

[0028] The second aspect of the present application provides a method for preparing a composite negative electrode material, comprising:

[0029] reacting acrylate with acrylic acid, hydroxylated carbon nanotubes, and a silicon-based material matrix to obtain a pre-reacted mixture; and

[0030] The pre-reacted mixture is polymerized with acrylonitrile and acrylic acid polyether polyol monoester to form a polymer structure coated on at least part of the surface of the silicon-based material matrix to obtain a composite negative electrode material, wherein the composite negative electrode material comprises the silicon-based material matrix and the polymer structure, the polymer structure comprises an organic polymer and the hydroxylated carbon nanotubes, at least part of the organic polymer is combined with the hydroxylated carbon nanotubes to form a composite, and the organic polymer comprises a compound having a structure shown in formula (1).

[0031]

[0032] In formula (1), m is an integer of 2500 to 20000, and R1 is a polymerized unit containing an ester group and a nitrile group.

[0033] In the method provided in the present application, by first pre-reacting acrylate with acrylic acid, hydroxylated carbon nanotubes, and a silicon-based material matrix, pre-polymerization of acrylate, acrylic acid, hydroxylated carbon nanotubes, and a silicon-based material matrix can be achieved, so that part of the acrylate and acrylic acid form oligomers through pre-polymerization, and part of the hydroxylated carbon nanotubes are also grafted onto the oligomer and / or the silicon-based material matrix through an esterification reaction to obtain a pre-reacted mixture; then the pre-reacted mixture is polymerized with acrylonitrile and acrylic acid polyether polyol monoester to achieve linear polymerization of the pre-reacted mixture, acrylonitrile, and acrylic acid polyether polyol monoester to form an organic polymer having a structural formula shown in formula (1), and part of the organic polymer is grafted onto the silicon-based material matrix through an esterification reaction; at the same time, more hydroxylated carbon nanotubes can be grafted onto the organic polymer through an esterification reaction, thereby combining with the organic polymer to form a composite, and the composite is also grafted onto the silicon-based material matrix through an esterification reaction. Among them, polyacrylic acid and polyacrylonitrile formed after the polymerization of acrylic acid and acrylonitrile both have good bonding effects. The polymerization of the two can play a reinforcing role, which is beneficial to give full play to the coating and connection effect of the polymerization structure on the silicon-based material, enhance the coating and binding effect on the silicon-based material, and improve the inhibitory effect on the volume expansion of the silicon-based material during the cycle, reduce the rebound of the electrode, reduce the expansion force during the cycle of the battery cell, and improve the cycle life of the battery cell.

[0034] In some embodiments of the present application, acrylate is reacted with acrylic acid, hydroxylated carbon nanotubes, and a silicon-based material matrix, comprising:

[0035] Under the action of a polymerization aid, the acrylate, the acrylic acid, the hydroxylated carbon nanotubes and the silicon-based material matrix are contacted and reacted.

[0036] While acting as a surfactant, the polymerization aid can also break the hydrogen bonds within and between molecules, which is beneficial to promoting the prepolymerization reaction.

[0037] In some embodiments of the present application, the method satisfies at least one of the following conditions:

[0038] (1) The acrylate comprises at least one of sodium acrylate, potassium acrylate, lithium acrylate and ammonium acrylate;

[0039] (2) The polymerization aid includes sodium dodecyl sulfonate and / or sodium dodecyl sulfate;

[0040] (3) The silicon-based material includes at least one of elemental silicon, silicon-oxygen compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys; and

[0041] (4) The hydroxylated carbon nanotubes include hydroxylated single-walled carbon nanotubes and / or hydroxylated multi-walled carbon nanotubes.

[0042] The silicon-based material is a modified silicon-based material with hydroxyl and / or carboxyl groups grafted on the surface of the silicon-based material, and the hydroxylated carbon nanotube is a carbon nanotube with hydroxyl groups grafted on the surface of the carbon nanotube; the selection of the silicon-based material and the hydroxylated carbon nanotube can realize a prepolymerization reaction.

[0043] In some embodiments of the present application, under the action of a polymerization aid, the acrylate, the acrylic acid, the hydroxylated carbon nanotubes and the silicon-based material matrix are contacted and reacted, comprising:

[0044] The polymerization aid, the acrylate, the acrylic acid, the hydroxylated carbon nanotubes and the silicon-based material matrix are contacted and mixed in water to form a first mixed solution;

[0045] The first mixed liquid is subjected to a first heat treatment so as to cause a prepolymerization reaction between the acrylate, the acrylic acid, the hydroxylated carbon nanotubes and the silicon-based material matrix.

[0046] In the above steps, after the first mixed liquid consisting of the polymerization aid, acrylate, acrylic acid, hydroxylated carbon nanotubes and silicon-based material matrix is ​​subjected to the first heat treatment, part of the acrylate and acrylic acid can form oligomers through a prepolymerization reaction, and part of the hydroxylated carbon nanotubes can also be grafted onto the oligomer and / or the silicon-based material matrix through an esterification reaction to obtain a pre-reacted mixture.

[0047] In some embodiments of the present application, the method satisfies at least one of the following conditions:

[0048] (1) In the first mixed solution, the mass percentage of the acrylate is 10% to 30%, and can be optionally 20% to 25%;

[0049] (2) In the first mixed solution, the mass percentage of the acrylic acid is 20% to 40%, and can be optionally 25% to 35%;

[0050] (3) In the first mixed solution, the mass percentage of the hydroxylated carbon nanotubes is 1% to 3%, and can be optionally 2% to 2.5%;

[0051] (4) In the first mixed solution, the mass percentage of the polymerization aid is 2% to 5%, and can be optionally 3% to 4.5%;

[0052] (5) In the first mixed solution, the mass percentage of the silicon-based material matrix is ​​10% to 80%

[0053] (6) The temperature of the first heat treatment is 50°C to 85°C, and can be optionally 65°C to 75°C.

[0054] The mass percentage of the silicon-based material matrix in the first mixed solution is within a suitable range, which is conducive to ensuring that the mass percentage of the silicon-based material matrix in the final composite negative electrode material is within a suitable range, thereby ensuring that the polymer structure has a good coating and connection effect on the silicon-based material matrix, thereby effectively inhibiting the volume expansion of the silicon-based material; and ensuring that the composite negative electrode material has a high capacity. The mass percentage of the hydroxylated carbon nanotubes in the first mixed solution is within a suitable range, which is conducive to consuming the carboxyl functional groups in the mixed solution through esterification reaction, thereby effectively reducing the carboxyl functional groups contained in the final organic polymer, reducing the agglomeration formed by hydrogen bonding between long polymer chains, improving the dispersion uniformity, and improving the dynamic performance of the battery cell.

[0055] In some embodiments of the present application, the pre-reacted mixture is polymerized with acrylonitrile and acrylic polyether polyol monoester, comprising:

[0056] Under the action of a polymerization initiator, the pre-reacted mixture is brought into contact with the acrylonitrile and the acrylic polyether polyol monoester and polymerized to form the polymerization unit, wherein the polymerization unit includes a polymerization unit of the structural formula shown in formula (2),

[0057]

[0058] In formula (2), ** represents the connection site of the polymer unit, p is an integer from 1000 to 5000, q is an integer from 1000 to 15000, f is an integer from 500 to 4000, 2≤n≤200, each R2 is independently selected from and One of the following, * indicates the connection site of R2, M + Selected from Na + , K + , Li + and NH4 + One of them.

[0059] The polymerization under the action of a polymerization initiator is conducive to initiating and promoting the polymerization reaction, forming the polymerization unit of the above formula (2) to obtain an organic polymer.

[0060] In some embodiments of the present application, the method satisfies at least one of the following conditions:

[0061] (1) the acrylic acid polyether polyol monoester comprises at least one of acrylic acid polyethylene glycol monoester, acrylic acid polypropylene glycol monoester and acrylic acid polytetrahydrofuran diol monoester; and

[0062] (2) The polymerization initiator includes at least one of potassium sulfate, potassium persulfate and sodium persulfate.

[0063] Selecting a suitable type of acrylic acid polyether polyol monoester can promote the polymerization reaction and obtain a polymerization structure of acrylic acid polyether polyol monoester in the composite negative electrode material.

[0064] In some embodiments of the present application, under the action of a polymerization initiator, the pre-reacted mixture is brought into contact with the acrylonitrile and the acrylic polyether polyol monoester and polymerized, comprising:

[0065] Contacting and mixing the polymerization initiator, the acrylonitrile and the acrylic polyether polyol monoester in the solution of the pre-reacted mixture to obtain a second mixed solution;

[0066] The second mixed liquid is subjected to a second heat treatment to allow the acrylonitrile, the acrylic polyether polyol monoester and the pre-reacted mixture to undergo a polymerization reaction.

[0067] In the above steps, the pre-reacted mixture is polymerized with acrylonitrile and acrylic polyether polyol monoester, so that the pre-reacted mixture, acrylonitrile and acrylic polyether polyol monoester can be linearly polymerized to form an organic polymer having the structural formula shown in formula (1), and part of the organic polymer is grafted onto the silicon-based material matrix through an esterification reaction; at the same time, more hydroxylated carbon nanotubes can be grafted onto the organic polymer through an esterification reaction, thereby combining with the organic polymer to form a composite, and the composite is also grafted onto the silicon-based material matrix through an esterification reaction.

[0068] In some embodiments of the present application, the method satisfies at least one of the following conditions:

[0069] (1) In the second mixed solution, the mass percentage of the polymerization initiator is 1% to 3%, and can be optionally 2% to 2.5%;

[0070] (2) In the second mixed liquid, the mass percentage of acrylonitrile is 4% to 8%, and can be optionally 5% to 7%;

[0071] (3) In the second mixed solution, the mass percentage of the acrylic polyether polyol monoester is 10% to 30%, and can be optionally 20% to 25%;

[0072] (4) The temperature of the second heat treatment is 50°C to 85°C, and can be optionally 65°C to 75°C.

[0073] The mass percentage of acrylic acid polyether polyol monoester in the second mixed liquid is controlled within an appropriate range, which is conducive to the formation of organic polymers and obtaining a polymerization structure of acrylic acid polyether polyol monoester with a corresponding degree of polymerization in the organic polymer, thereby promoting the formation of a corresponding polymerization structure in the composite negative electrode material, so that the polymerization structure can effectively play a coating and restraining role on the volume expansion of the silicon-based material matrix; it can also give full play to the coating effect of the linear polymerization of the organic polymer, synergistically enhance the bonding and coating effect of the binder in the slurry on other particulate matter, and reduce the rebound of the electrode under high compaction density; it can also make the composite negative electrode material have better solubility and dispersibility in the slurry.

[0074] In some embodiments of the present application, the step of preparing the acrylic polyether polyol monoester is also included:

[0075] Acrylic acid is contacted with polyether polyol to undergo an esterification reaction, thereby obtaining the acrylic acid polyether polyol monoester.

[0076] Acrylic acid polyether polyol monoester can be obtained by esterifying acrylic acid with polyether polyol, wherein the ether bonds contained in the acrylic acid polyether polyol monoester can effectively enhance the flexibility of the polymer structure in the composite negative electrode material, thereby enhancing the flexibility of the composite negative electrode material, thereby enhancing the flexibility of the electrode sheet containing the composite negative electrode material and improving the processability of the electrode sheet.

[0077] In some embodiments of the present application, the method satisfies at least one of the following conditions:

[0078] (1) the polyether polyol comprises at least one of polyethylene glycol, polypropylene glycol and polytetrahydrofuran diol; and

[0079] (2) The degree of polymerization of the polyether polyol is 2 to 200, and can be 50 to 150.

[0080] The degree of polymerization of polyether polyols is mainly reflected in the length of the side chain. A suitable degree of polymerization can improve the problem of brittle electrode caused by the linear structure of the main chain, but too long a degree of polymerization can easily lead to problems such as decreased adhesion and slurry processing.

[0081] In some embodiments of the present application, acrylic acid is contacted with a polyether polyol and an esterification reaction occurs, comprising:

[0082] The acrylic acid and the polyether polyol are contacted and mixed in water to form a third mixed solution;

[0083] The third mixed liquid is subjected to a third heat treatment to obtain a solution of the acrylic polyether polyol monoester.

[0084] In the above steps, acrylic acid and polyether polyol can undergo esterification reaction under the action of a catalyst and an inhibitor. The esterification reaction can link the carboxyl group in acrylic acid with the hydroxyl group in polyether polyol to form acrylic acid polyether polyol monoester.

[0085] In some embodiments of the present application, the method satisfies at least one of the following conditions:

[0086] (1) the molar ratio of the acrylic acid to the polyether polyol is (5:1) to (1:1), and may be (1.5:1) to (2.5:1); and

[0087] (2) The temperature of the third heat treatment is 50°C to 85°C, and can be optionally 65°C to 75°C.

[0088] The molar ratio of acrylic acid to polyether polyol is controlled within a suitable range, which is conducive to the occurrence of esterification reaction, thereby obtaining the target product acrylic acid polyether polyol monoester. The temperature of the third heat treatment is controlled within a suitable range, which is conducive to promoting the esterification reaction.

[0089] In some embodiments of the present application, before the third mixed liquid is subjected to the third heat treatment, the method further comprises:

[0090] adding a catalyst and an inhibitor to the third mixed liquid;

[0091] Optionally, the catalyst comprises at least one of p-toluenesulfonic acid, sulfuric acid and aluminum oxide; and

[0092] Optionally, the polymerization inhibitor includes at least one of hydroquinone, p-hydroxyanisole and 2,6-di-tert-butyl-p-cresol.

[0093] The appropriate type of catalyst can play a good catalytic role in the esterification reaction and increase the reaction rate; the appropriate type of inhibitor can play a role in preventing the polymerization of acrylic acid monomers in the esterification reaction.

[0094] In some embodiments of the present application, the method satisfies at least one of the following conditions:

[0095] (1) In the third mixed solution, the mass percentage of the catalyst is 3% to 10%, and can be 5% to 9%; and

[0096] (2) In the third mixed solution, the mass percentage of the polymerization inhibitor is 1% to 5%, and can be optionally 3% to 4.5%.

[0097] The mass percentage of the catalyst in the third mixed solution is within an appropriate range, so that the catalyst can play a better role in catalytic promotion. The mass percentage of the polymerization inhibitor in the third mixed solution is within an appropriate range, so that the polymerization inhibitor can play a better role in preventing the polymerization of acrylic acid monomers.

[0098] In some embodiments of the present application, after the third mixed liquid is subjected to the third heat treatment, the method further comprises:

[0099] The acrylic acid polyether polyol monoester solution is purified to obtain the acrylic acid polyether polyol monoester.

[0100] Purification treatment of the acrylic acid polyether polyol monoester solution can remove impurities in the reaction and obtain the target product acrylic acid polyether polyol monoester.

[0101] In some embodiments of the present application, the step of preparing the acrylate is also included:

[0102] Acrylic acid is contacted with an alkaline agent to react to obtain the acrylic acid salt.

[0103] Acrylic acid is salified by reacting acrylic acid with an alkaline reagent to obtain acrylate. By salifying the carboxylic acid functional group in acrylic acid, the hydrogen bonding effect on the polyacrylate molecular chain can be reduced during the subsequent polymerization reaction, and the mutual agglomeration between the molecular chains can be weakened, so that the final composite negative electrode material can be evenly dispersed in the slurry, thereby improving the kinetic performance of the battery cell.

[0104] In some embodiments of the present application, the step of allowing acrylic acid to contact with an alkaline agent comprises:

[0105] Adding an alkaline agent to a solution of acrylic acid to adjust the pH value of the solution to 7-8, thereby obtaining a solution of the acrylate; and

[0106] The acrylate solution is subjected to distillation and drying treatment.

[0107] In the above steps, the amount of reactants acrylic acid and alkaline reagent can be indirectly controlled by controlling the pH value of the solution. By controlling the amount of the reactants within a suitable range, the salification reaction is facilitated, thereby obtaining the target product acrylate.

[0108] In some embodiments of the present application, the method satisfies at least one of the following conditions:

[0109] (1) the alkaline reagent comprises at least one of sodium hydroxide, potassium hydroxide, lithium hydroxide and ammonia water; and

[0110] (2) The acrylate salt includes at least one of sodium acrylate, potassium acrylate, lithium acrylate and ammonium acrylate.

[0111] Acrylate can realize polymerization reaction in the subsequent process and obtain the polymerization structure of polyacrylate in the composite negative electrode material; the alkaline reagent can salt the acrylic acid and thus reduce the carboxyl group contained in the acrylic acid.

[0112] The third aspect of the present application provides a negative electrode plate, comprising the composite negative electrode material described in the first aspect of the present application or the composite negative electrode material prepared by the method described in the second aspect of the present application.

[0113] The fourth aspect of the present application provides a secondary battery, comprising the negative electrode sheet described in the third aspect of the present application.

[0114] A fifth aspect of the present application provides an electrical device, comprising the secondary battery described in the fourth aspect of the present application.

[0115] The electric device of the present application includes the secondary battery provided by the present application, and thus has at least the same advantages as the secondary battery.

[0116] The details of one or more embodiments of the present application are set forth in the following drawings and description. Other features, objects, and advantages of the present application will become apparent from the description, drawings, and claims. BRIEF DESCRIPTION OF THE DRAWINGS

[0117] Figure 1 It is a schematic diagram of one embodiment of the secondary battery of the present application.

[0118] Figure 2 It is an exploded schematic diagram of one embodiment of the secondary battery of the present application.

[0119] Figure 3 It is a schematic diagram of another embodiment of the secondary battery of the present application.

[0120] Figure 4 is a schematic diagram of another embodiment of the secondary battery of the present application.

[0121] Figure 5 yes Figure 4 Exploded diagram of .

[0122] Figure 6 It is a schematic diagram of an embodiment of an electric device using a secondary battery as a power source of the present application. DETAILED DESCRIPTION

[0123] In order to make the purpose, technical scheme and advantages of the present application clearer, the technical scheme of the present application will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present application, rather than all the embodiments. The relevant embodiments described herein are illustrative and are used to provide a basic understanding of the present application. The embodiments of the present application should not be interpreted as limiting the present application.

[0124] For simplicity, only some numerical ranges are specifically disclosed herein. However, any lower limit can be combined with any upper limit to form an unspecified range; and any lower limit can be combined with other lower limits to form an unspecified range, and any upper limit can be combined with any other upper limit to form an unspecified range. In addition, each separately disclosed point or single value can itself be combined as a lower limit or upper limit with any other point or single value or with other lower limits or upper limits to form an unspecified range.

[0125] In the description herein, unless otherwise specified, “above” and “below” include the number.

[0126] Unless otherwise specified, the terms used in this application have the commonly known meanings generally understood by those skilled in the art. Unless otherwise specified, the numerical values ​​of the various parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the examples of this application).

[0127] A list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single component or multiple components. Item B may contain a single component or multiple components. Item C may contain a single component or multiple components.

[0128] At present, in order to meet market demand, the energy density of secondary batteries represented by lithium-ion batteries is getting higher and higher. In this case, the design of the battery cell requires that the pole piece must have a high coating surface density and a high compaction density; at the same time, in order to improve the energy density, the secondary battery also introduces silicon-based materials in the selection of active materials. The inventor found in the research process that silicon-based materials will produce volume expansion during the cycle of the secondary battery. At the same time, accompanied by the conditions of high coating surface density and high compaction density, the pole piece will continue to accumulate in the direction perpendicular to the plane (Z direction), which will affect the amount of active material entering the shell in the short term, thereby affecting the capacity of the secondary battery; in the long term, the pole piece rebound will cause the expansion force of the battery cell to be too large, affecting the cycle life of the secondary battery. At the same time, silicon-based materials generally have the problem of low conductivity, which will also lead to low conductivity of secondary batteries using silicon-based materials.

[0129] In addition, conventional secondary batteries represented by lithium-ion batteries generally use organic polymers as binders. Among them, compared with other types of binders, polyacrylic acid polymers, as a single type of monomer linear polymer, are more widely used in secondary batteries due to their high adhesion and chemical stability. However, the inventors found in the research process that although the overall performance of polyacrylic acid polymers is better than other similar binders, when polyacrylic acid polymers are used as binders alone, the long polymer chains will agglomerate with each other due to the hydrogen bonding between molecules on the long polymer chains, and the binder is difficult to effectively disperse in the slurry, which ultimately leads to an increase in the resistance of the electrode sheet, an increase in the DC resistance (DCR) of the battery cell, and lithium precipitation, and its kinetic performance deteriorates.

[0130] In addition, the inventors also found that although polyacrylic acid polymers have excellent bonding properties, their conductivity is poor; and this single type of monomer linear polymer is generally brittle due to the relatively simple types of functional groups, and is usually in contact with other particulate matter in the slurry in the form of a mesh surface contact. After the above slurry is applied to the current collector to form a pole piece, the linear structure of the polyacrylic acid polymer molecular chain will make the pole piece insufficiently flexible. After cold pressing at a high compaction density, the pole piece will have insufficient ductility, and stress will easily concentrate at the edge of the coating area, thereby causing overpressure at the edge; at the same time, the pole piece under high density is prone to brittle fracture in the subsequent processing, resulting in poor machinability of the pole piece.

[0131] Furthermore, in the process of pursuing high energy and high power density in secondary batteries represented by lithium-ion batteries, linear CNTs (carbon nanotubes) have become the main additives in the positive and negative electrode slurry formulas due to their high conductivity. However, the inventors found that during the preparation of the slurry containing linear CNTs, the linear CNTs will produce cross-linking, which will cause the CNTs to entangle in the slurry, resulting in uneven dispersion of the slurry and even gelation, thereby affecting the processability of the electrode.

[0132] In order to solve the above problems, the inventors started from silicon-based materials, linear polymer binders and linear CNT conductive agents, and proposed a composite negative electrode material through extensive research, including a silicon-based material matrix and a polymer structure coated on at least part of the surface of the silicon-based material matrix, the polymer structure includes an organic polymer and a hydroxylated carbon nanotube, and at least part of the organic polymer is combined with the hydroxylated carbon nanotube to form a composite. In the above composite negative electrode material, the surface of the silicon-based material matrix is ​​coated with a polymer structure, and the organic polymer in the polymer structure and the hydroxylated CNT can fully realize linear polymerization to form a composite. The composite can give full play to the coating effect of linear polymerization and play a good restraining role on the volume expansion of the silicon-based material, thereby reducing the rebound of the pole piece and improving the cycle life of the battery cell; at the same time, the hydroxylated CNT in the polymer structure can also make up for the resistance deterioration caused by the coating and improve the conductivity of the composite negative electrode material. In addition, after the surface of the silicon-based material substrate is coated with the connected polymer structure, the polymer structure can also reduce the contact area between the silicon-based material and the electrolyte, reduce the corrosion of the electrolyte on the silicon-based material, and effectively protect the surface of the silicon-based material, thereby improving the performance of the silicon-based material during the cycle or storage process and further improving the cycle life of the battery cell.

[0133] In addition, in the composite negative electrode material, the organic polymer is combined with the hydroxylated carbon nanotube to form a composite. During the slurry processing, the long-chain molecules of the organic polymer can be suspended in the aqueous solution, which plays a role in stabilizing other particulate matter in the slurry, thereby playing a thickening and stabilizing role of the linear organic polymer, improving the distribution state of the hydroxylated CNT in the slurry, and improving the uniformity of dispersion. At the same time, after combining the silicon-based material, the organic polymer and the hydroxylated CNT, the high conductivity of the hydroxylated CNT can also improve the conductive properties of the silicon-based material and the organic polymer, thereby obtaining a composite negative electrode material with better conductive properties. In addition, the organic polymer and the hydroxylated CNT in the composite negative electrode material also fully realize linear polymerization, thereby fully exerting the coating effect of linear polymerization, synergistically enhancing the bonding and coating effect of the binder in the slurry on other particulate matter, reducing the rebound of the pole piece under high compaction density, reducing the expansion force during the battery cell cycle, and improving the cycle life of the battery cell.

[0134] Composite negative electrode materials

[0135] A first aspect of the embodiments of the present application provides a method comprising a silicon-based material substrate and a polymer structure coated and connected to at least a portion of the surface of the silicon-based material substrate, wherein the polymer structure comprises an organic polymer and hydroxylated carbon nanotubes, at least a portion of the organic polymer is combined with the hydroxylated carbon nanotubes to form a composite, and the organic polymer comprises a compound having a structure shown in formula (1),

[0136]

[0137] In the formula (1), m is an integer of 2500 to 20000, and R1 is a polymerized unit containing an ester group and a nitrile group.

[0138] In the embodiment of the present application, the composite negative electrode material includes a silicon-based material matrix and a polymer structure connected to the surface of the silicon-based material matrix, wherein the organic polymer in the polymer structure and the hydroxylated CNT can fully realize linear polymerization to form a composite, and the composite can give full play to the coating effect of linear polymerization, and play a good inhibitory and restraining role on the volume expansion of the silicon-based material, thereby reducing the rebound of the pole piece and improving the cycle life of the battery cell. At the same time, the hydroxylated CNT in the polymer structure can also make up for the resistance deterioration caused by the coating and improve the conductivity of the composite negative electrode material. In addition, after the surface of the silicon-based material matrix is ​​coated and connected to the polymer structure, the contact area between the silicon-based material and the electrolyte can be reduced, the corrosion of the electrolyte to the silicon-based material can be reduced, and the surface of the silicon-based material can be effectively protected, thereby improving the performance of the silicon-based material during the cycle or storage process, and further improving the cycle life of the battery cell.

[0139] In addition, the composite negative electrode material includes a composite formed by combining an organic polymer and a hydroxylated carbon nanotube, wherein the organic polymer includes a linear polymerization structure of the structural formula shown in the above formula (1), and the hydroxylated carbon nanotube is also a linear structure, and the composite formed by combining the two can fully realize linear polymerization. Therefore, when the composite negative electrode material is used to prepare the electrode slurry, the composite negative electrode material can also give full play to the coating effect of linear polymerization, synergistically enhance the binding and binding effect of the binder (such as polyacrylic acid binder) in the slurry on other particulate matter, improve the inhibitory effect on the volume expansion of other particulate matter during the cycle process, reduce the rebound of the electrode, reduce the expansion force during the cycle of the battery cell, and further improve the cycle life of the battery cell.

[0140] In addition, since the composite negative electrode material contains organic polymers, and the organic polymers can play a good thickening and stabilizing role in the slurry, its long-chain molecules can be suspended in the aqueous solution, playing a role in stabilizing other particulate matter in the slurry. Therefore, compared with the traditional linear CNT (carbon nanotube), the composite negative electrode material can promote the stabilizing effect of the organic polymer on the linear carbon nanotubes by combining the organic polymer with the hydroxylated carbon nanotubes to form a composite, reduce the cross-linking entanglement of the carbon nanotubes, improve the distribution state of the carbon nanotubes in the slurry, and improve its dispersion uniformity, thereby further improving the processability of the pole piece and improving the fast charging performance of the battery cell. At the same time, compared with the traditional organic high molecular polymer binder, by combining the silicon-based material, the organic polymer and the hydroxylated carbon nanotube, the high conductivity of the carbon nanotube can also improve the conductivity of the silicon-based material and the organic polymer, thereby obtaining a composite negative electrode material with better conductivity.

[0141] In some embodiments, the polymeric unit comprises a polymeric unit of the structural formula shown in formula (2),

[0142]

[0143] In formula (2), ** represents the connection site of the polymer unit, p is an integer from 1000 to 5000, q is an integer from 1000 to 15000, f is an integer from 500 to 4000, 2≤n≤200, each R2 is independently selected from and One of the following, * indicates the connection site of R2, M + Selected from Na + , K + , Li + and NH4 + One of them.

[0144] It can be seen from the above formula (2) that, compared with the traditional single-type monomer linear polymer, in the composite negative electrode material of the present application, the linear structure of the molecular chain contained in the polymerization unit contains more side chains composed of multiple different functional groups. These side chains can reduce the brittleness of the composite negative electrode material and enhance its flexibility, thereby enhancing the flexibility of the electrode piece; thus, after high compaction density cold pressing, the ductility of the electrode piece can be improved, which can effectively reduce the occurrence of edge overpressure; at the same time, it can also improve the phenomenon that the electrode piece under high density is prone to brittle fracture during subsequent processing, thereby improving the processability of the electrode piece.

[0145] In some embodiments, in the structural formula (1) of the organic polymer, the polymerization degree m, p, q, and f of each polymer structure will affect the coating effect of the polymer structure on the silicon-based material, as well as the adhesion and solubility and dispersibility of the composite negative electrode material in the slurry. When the polymerization degree of each polymer structure is relatively low, it is not easy to fully exert the coating effect of the linear polymerization of the polymer structure, and the volume expansion of the silicon-based material cannot be effectively inhibited and bound, and the adhesion of the composite negative electrode material is easily reduced; when the polymerization degree of each polymer structure is relatively high, the solubility and dispersibility of the composite negative electrode material in the slurry is easily reduced. By controlling the polymerization degree m, p, q, and f of each polymer structure within a suitable range, the polymer structure can have a good inhibitory and binding effect on the silicon-based material, and the composite negative electrode material has a higher adhesion performance, and the composite negative electrode material can have a better solubility and dispersibility in the slurry.

[0146] In some embodiments, the polymeric structure is connected to at least a portion of the surface of the silicon-based material substrate via an ester group and / or a hydrogen bond. Alternatively, the polymeric structure is connected to at least a portion of the surface of the silicon-based material substrate via an ester group.

[0147] In some embodiments, the silicon-based material matrix contains hydroxyl functional groups and / or carboxyl functional groups.

[0148] It is understandable that the above-mentioned ester group can be obtained by esterification reaction between the hydroxyl functional group and / or carboxyl functional group contained in the silicon-based material matrix and the carboxyl functional group and / or hydroxyl functional group in the polymer structure. As a non-limiting example of the ester group, the above-mentioned ester group can be obtained by esterification reaction between the hydroxyl functional group contained in the silicon-based material matrix and the carboxyl functional group in the organic polymer, or by esterification reaction between the carboxyl functional group contained in the silicon-based material matrix and the hydroxyl group in the hydroxylated carbon nanotube, or by esterification reaction between the hydroxyl functional group and / or carboxyl functional group contained in the silicon-based material matrix and the carboxyl functional group and / or hydroxyl functional tube in the composite. The polymer structure is connected to at least part of the surface of the silicon-based material matrix through the ester group, so that the polymer bond on the surface of the composite negative electrode material is not easy to fall off, thereby enhancing the firmness of the coating connection of the polymer structure to the silicon-based material, so as to better exert the inhibitory and restraining effect of the polymer structure on the volume expansion of the silicon-based material.

[0149] As a non-limiting example of a composite in a composite negative electrode material, a schematic structural formula of the composite may include any one of the following formulas (3) to (8):

[0150]

[0151]

[0152] In some embodiments, the organic polymer in the composite is bonded to the hydroxylated carbon nanotube via an ester group and / or a hydrogen bond. Alternatively, the organic polymer in the composite is bonded to the hydroxylated carbon nanotube via an ester group.

[0153] It is understandable that the ester group in the composite can be obtained by esterification reaction between the hydroxyl functional group in the hydroxylated carbon nanotube and the carboxyl functional group in the organic polymer. After the ester group is formed between the hydroxylated carbon nanotube and the organic polymer, the carboxyl functional group in the organic polymer can be reduced, thereby reducing the hydrogen bonding effect between molecules on the long polymer chain, effectively reducing the mutual agglomeration between the long polymer chains, improving the dispersion uniformity of the composite negative electrode material in the slurry, reducing the electrode sheet resistance, and thus improving the dynamic performance of the battery cell.

[0154] In some embodiments, the type of the silicon-based material is not particularly limited and can be selected according to actual needs. For example, the silicon-based material can include at least one of elemental silicon, silicon-oxygen compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys.

[0155] It should be noted that the silicon-based material in the present application is a modified silicon-based material having hydroxyl groups and / or carboxyl groups grafted on the surface of the silicon-based material. For example, the silicon-based material containing hydroxyl groups and / or carboxyl groups can be obtained by acid washing the silicon-based material.

[0156] In some embodiments, the hydroxylated carbon nanotubes include hydroxylated single-walled carbon nanotubes and / or hydroxylated multi-walled carbon nanotubes.

[0157] In some embodiments, at least one hydroxyl group is connected to the surface of the hydroxylated carbon nanotube. Optionally, the hydroxylated carbon nanotube includes a hydroxylated single-walled carbon nanotube and / or a hydroxylated multi-walled carbon nanotube.

[0158] It should be noted that the hydroxylated carbon nanotubes described in the present application are carbon nanotubes having at least one hydroxyl group on the surface, and these hydroxyl groups can be attached to the surface of the carbon nanotubes by methods including but not limited to grafting. As a non-limiting example of hydroxylated carbon nanotubes, the hydroxylated carbon nanotubes can be commercial hydroxylated carbon nanotubes, or can be obtained by acid washing carbon nanotubes.

[0159] In some embodiments, in the composite negative electrode material, the mass percentage of the silicon-based material matrix is ​​15% to 90%, for example, the mass percentage of the silicon-based material matrix can be 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85% or within the range of any of the above values. Optionally, the mass percentage of the silicon-based material matrix is ​​40% to 85%.

[0160] The mass percentage of the silicon-based material matrix in the composite negative electrode material is within an appropriate range, which can ensure that the polymer structure has a good coating and connection effect on the silicon-based material matrix, thereby effectively inhibiting the volume expansion of the silicon-based material; and can also ensure that the composite negative electrode material has a higher capacity.

[0161] In some embodiments, in the composite negative electrode material, the mass percentage of the organic polymer is 6% to 60%, for example, the mass percentage of the organic polymer can be 10%, 20%, 30%, 40%, 50% or within the range of any of the above values. Optionally, the mass percentage of the organic polymer is 15% to 25%.

[0162] The mass percentage of the organic polymer in the composite negative electrode material is within an appropriate range, which can provide sufficient linear polymer structure for forming a composite in the polymer structure, ensure the full performance of the organic polymer, improve the cycle life of the battery cell and the processability of the electrode; and ensure that the composite negative electrode material has high conductivity.

[0163] In some embodiments, in the composite negative electrode material, the mass percentage of the composite is 10% to 80%, for example, the mass percentage of the composite can be 20%, 30%, 40%, 50%, 60%, 70% or within the range of any of the above values. Optionally, the mass percentage of the composite is 20% to 50%.

[0164] The mass percentage of the composite in the composite negative electrode material is within an appropriate range, which can not only promote the polymer structure to better coat and connect the silicon-based material matrix, thereby effectively inhibiting the volume expansion of the silicon-based material; it can also make the carboxyl functional groups in the organic polymer be sufficiently consumed due to the formation of a composite with a corresponding mass content, thereby effectively reducing the carboxyl functional groups in the organic polymer, reducing the agglomeration formed by hydrogen bonding between long polymer chains, improving the dispersion uniformity, and improving the kinetic performance of the battery cell.

[0165] The mass percentage of each component in the composite negative electrode material is a well-known meaning in the art and can be measured using instruments and methods known in the art. For example, the percentage of the organic polymer part can be measured by acid washing and filtration, and the remaining solid phase can be separated by high-temperature ultrasonic method. The percentage of CNT and silicon-based materials can be roughly calculated by multiple standing and removing the upper suspension.

[0166] A second aspect of the present application provides a method for preparing a composite negative electrode material, comprising the following steps:

[0167] S10, reacting acrylate with acrylic acid, hydroxylated carbon nanotubes, and a silicon-based material matrix to obtain a pre-reacted mixture; and

[0168] S20, polymerizing the pre-reacted mixture with acrylonitrile and acrylic acid polyether polyol monoester to form a polymer structure coated on at least part of the surface of the silicon-based material matrix to obtain a composite negative electrode material, wherein the composite negative electrode material includes the silicon-based material matrix and the polymer structure, the polymer structure includes an organic polymer and the hydroxylated carbon nanotubes, at least part of the organic polymer is combined with the hydroxylated carbon nanotubes to form a composite, and the organic polymer includes a compound with a structure shown in formula (1),

[0169]

[0170] In formula (1), m is an integer from 2500 to 20000, and R1 is a polymerized unit containing an ester group and a nitrile group.

[0171] In the method provided in the present application, by first pre-reacting acrylate with acrylic acid, hydroxylated carbon nanotubes, and a silicon-based material matrix, pre-polymerization of acrylate, acrylic acid, hydroxylated carbon nanotubes, and a silicon-based material matrix can be achieved, so that part of the acrylate and acrylic acid form oligomers through pre-polymerization, and part of the hydroxylated carbon nanotubes are also grafted onto the oligomer and / or the silicon-based material matrix through an esterification reaction to obtain a pre-reacted mixture; then the pre-reacted mixture is polymerized with acrylonitrile and acrylic acid polyether polyol monoester to achieve linear polymerization of the pre-reacted mixture, acrylonitrile, and acrylic acid polyether polyol monoester to form an organic polymer having a structural formula shown in formula (1), and part of the organic polymer is grafted onto the silicon-based material matrix through an esterification reaction; at the same time, more hydroxylated carbon nanotubes can be grafted onto the organic polymer through an esterification reaction, thereby combining with the organic polymer to form a composite, and the composite is also grafted onto the silicon-based material matrix through an esterification reaction. Among them, polyacrylic acid and polyacrylonitrile formed after the polymerization of acrylic acid and acrylonitrile both have good bonding effects. The polymerization of the two can play a reinforcing role, which is beneficial to give full play to the coating and connection effect of the polymerization structure on the silicon-based material, enhance the coating and binding effect on the silicon-based material, and improve the inhibitory effect on the volume expansion of the silicon-based material during the cycle, reduce the rebound of the electrode, reduce the expansion force during the cycle of the battery cell, and improve the cycle life of the battery cell.

[0172] In some implementations, the above step S10 may include the following steps:

[0173] S100, contacting and mixing the polymerization aid, the acrylate, the acrylic acid, the hydroxylated carbon nanotubes and the silicon-based material matrix in water to form a first mixed solution; and

[0174] S110, performing a first heat treatment on the first mixed liquid to cause a prepolymerization reaction between the acrylate, the acrylic acid, the hydroxylated carbon nanotubes and the silicon-based material matrix.

[0175] In the above steps S100 to S100, after the first heat treatment is performed on the first mixed solution composed of the polymerization aid, acrylate, acrylic acid, hydroxylated carbon nanotubes and silicon-based material matrix, part of the acrylate and acrylic acid can form oligomers through prepolymerization reaction, and part of the hydroxylated carbon nanotubes can also be grafted onto the oligomer and / or silicon-based material matrix through esterification reaction to obtain a pre-reacted mixture. Structurally, in the above pre-reaction, the hydroxylated carbon nanotubes and the silicon-based material are mainly connected with the acrylic acid part. The purpose of the prepolymerization reaction is to react the related components separately in advance, strengthen the connection effect, and avoid the interference of subsequent components causing the bond strength to decrease and the connection structure to be unstable; because acrylate and acrylic acid have similar structures, polymerization will be easier, so acrylate is introduced simultaneously for prepolymerization reaction.

[0176] In some embodiments, the type of the silicon-based material is not particularly limited, as long as it contains hydroxyl and / or carboxyl functional groups to achieve prepolymerization. For example, the silicon-based material may include at least one of elemental silicon, silicon-oxygen compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys.

[0177] In some embodiments, in the first mixed solution, the mass percentage of the silicon-based material matrix is ​​10% to 80%. For example, the mass percentage of the silicon-based material matrix can be 20%, 30%, 40%, 50%, 60%, 70% or within the range of any of the above values. The mass percentage of the silicon-based material matrix in the first mixed solution is within a suitable range, which is conducive to ensuring that the mass percentage of the silicon-based material matrix in the final composite negative electrode material is within a suitable range, thereby ensuring that the polymer structure has a good coating and connection effect on the silicon-based material matrix, thereby effectively suppressing the volume expansion of the silicon-based material; and ensuring that the composite negative electrode material has a higher capacity.

[0178] In some embodiments, the type of the acrylate is not particularly limited, as long as the prepolymerization reaction can be achieved and the polymer structure of the polyacrylate can be obtained in the organic polymer. For example, the acrylate may include at least one of sodium acrylate, potassium acrylate, lithium acrylate and ammonium acrylate.

[0179] In some embodiments, in the first mixed solution, the mass percentage of the acrylate is 3% to 25%. For example, the mass percentage of the acrylate can be 5%, 7%, 11%, 13%, 15%, 17%, 19%, 21%, 23% or within the range of any of the above values. Optionally, the mass percentage of the acrylate is 5% to 15%. The acrylate and acrylic acid monomers in the first mixed solution have similar molecular structures, and synchronous polymerization is beneficial to improving the reaction efficiency of the overall preparation process, while avoiding the introduction of too many types of monomer molecules into the subsequent polymerization reaction.

[0180] In some embodiments, in the first mixed solution, the mass percentage of the acrylic acid is 5% to 40%. For example, the mass percentage of acrylic acid can be 10%, 15%, 20%, 25%, 30%, 35% or within the range of any of the above values. Optionally, the mass percentage of acrylic acid is 15% to 25%. The mass percentage of acrylic acid in the first mixed solution is within a suitable range, which is conducive to obtaining a polyacrylic acid polymerization structure with a corresponding degree of polymerization in the organic polymer, thereby promoting the formation of a corresponding polymerization structure in the composite negative electrode material, so that the polymerization structure can effectively play a coating and restraining role on the volume expansion of the silicon-based material matrix, and can also make the composite negative electrode material have better solubility and dispersibility in the slurry.

[0181] In some embodiments, in the first mixed solution, the mass percentage of the hydroxylated carbon nanotubes is 1% to 10%. For example, the mass percentage of the hydroxylated carbon nanotubes can be 3%, 5%, 7%, 9% or within the range of any of the above values. Optionally, the mass percentage of the hydroxylated carbon nanotubes is 3% to 7%. The mass percentage of the hydroxylated carbon nanotubes in the first mixed solution is within a suitable range, which is conducive to consuming the carboxyl functional groups in the mixed solution through esterification reaction, thereby effectively reducing the carboxyl functional groups contained in the organic polymer finally formed, reducing the agglomeration formed by hydrogen bonding between long polymer chains, improving the uniformity of dispersion, and improving the dynamic performance of the battery cell.

[0182] In some embodiments, the type of polymerization aid is not particularly limited, as long as it can play the role of a surfactant in the prepolymerization reaction and can break the hydrogen bonds within and between molecules. For example, the polymerization aid can include sodium dodecyl sulfonate and / or sodium dodecyl sulfate.

[0183] In the first mixed solution, the mass percentage of the polymerization aid is 2% to 5%. For example, the mass percentage of the polymerization aid can be 2.5%, 3.0%, 3.5%, 4.0%, 4.5% or in the range of any of the above values. Optionally, the mass percentage of the polymerization aid is 3% to 4.5%. The mass percentage of the polymerization aid in the first mixed solution is within a suitable range, which not only reduces the surface tension and stabilizes the first mixed solution, but also helps to promote the prepolymerization reaction.

[0184] In some embodiments, the temperature of the first heat treatment is 50° C. to 85° C., and can be 65° C. to 75° C. The temperature of the first heat treatment is controlled within a suitable range, which is beneficial to further promote the prepolymerization reaction.

[0185] As a non-limiting example of step S10, sodium dodecyl sulfate, acrylic acid, sodium acrylate, hydroxylated CNT and silicon-based material matrix may be added to 1 kg of distilled water, stirred evenly and heated to 70° C. to obtain a pre-reacted mixture.

[0186] In some implementations, the above step S20 may include the following steps:

[0187] S200, contacting and mixing the polymerization initiator, the acrylonitrile and the acrylic polyether polyol monoester in the solution of the pre-reacted mixture to obtain a second mixed solution; and

[0188] S210, performing a second heat treatment on the second mixed liquid to cause a polymerization reaction between the acrylonitrile, the acrylic polyether polyol monoester and the pre-reacted mixture to form the polymerization unit, wherein the polymerization unit includes a polymerization unit of the structural formula shown in formula (2),

[0189]

[0190] In formula (2), ** represents the connection site of the polymer unit, p is an integer from 1000 to 5000, q is an integer from 1000 to 15000, f is an integer from 500 to 4000, 2≤n≤200, each R2 is independently selected from and One of the following, * indicates the connection site of R2, M + Selected from Na + , K + , Li + and NH4 + One of them.

[0191] In the above steps S200 to S210, the pre-reacted mixture is polymerized with acrylonitrile and acrylic polyether polyol monoester, so that the pre-reacted mixture, acrylonitrile and acrylic polyether polyol monoester can be linearly polymerized to form a polymerization unit including the structural formula shown in formula (2), and part of the organic polymer is grafted onto the silicon-based material matrix through an esterification reaction; at the same time, more hydroxylated carbon nanotubes can be grafted onto the organic polymer through an esterification reaction, thereby combining with the organic polymer to form a composite, and the composite is also grafted onto the silicon-based material matrix through an esterification reaction.

[0192] In some embodiments, the type of the acrylic acid polyether polyol monoester is not particularly limited, as long as the polymerization reaction can be achieved and the polymerization structure of the acrylic acid polyether polyol monoester can be obtained in the organic polymer. For example, the acrylic acid polyether polyol monoester can include at least one of acrylic acid polyethylene glycol monoester, acrylic acid polypropylene glycol monoester and acrylic acid polytetrahydrofuran diol monoester.

[0193] In some embodiments, in the second mixed solution, the mass percentage of the acrylic polyether polyol monoester is 10% to 40%. For example, the mass percentage of the acrylic polyether polyol monoester can be 15%, 20%, 25%, 30%, 35% or within the range of any of the above values. Optionally, the mass percentage of the acrylic polyether polyol monoester is 20% to 35%. The mass percentage of the acrylic polyether polyol monoester in the second mixed solution is controlled within a suitable range, which is conducive to the formation of organic polymers and obtaining a polyacrylic polyether polyol monoester polymerization structure of a corresponding degree of polymerization in the organic polymer, thereby promoting the formation of a corresponding polymerization structure in the composite negative electrode material, so that the polymerization structure can effectively play a coating and restraining role on the volume expansion of the silicon-based material matrix; it can also give full play to the coating effect of the linear polymerization of the organic polymer, synergistically enhance the bonding and coating effect of the binder in the slurry on other particulate matter, and reduce the rebound of the pole piece under high compaction density; it can also make the composite negative electrode material have better solubility and dispersibility in the slurry.

[0194] In some embodiments, the mass percentage of acrylonitrile in the second mixed solution is 5% to 30%. For example, the mass percentage of acrylonitrile can be 10%, 15%, 20%, 25% or within the range of any of the above values. Optionally, the mass percentage of acrylonitrile is 10% to 20%.

[0195] The mass percentage of acrylonitrile in the second mixed liquid is within an appropriate range, which is conducive to obtaining a polyacrylonitrile polymerization structure with a corresponding degree of polymerization in the organic polymer. Since the polyacrylonitrile formed after the polymerization of acrylonitrile has a good bonding effect, it can enhance the bonding properties of the polyacrylic acid polymerization structure in the organic polymer, which is conducive to fully exerting the coating and restraining effect on the volume expansion of the silicon-based material matrix, and can synergistically enhance the bonding and restraining effect on other particulate matter in the slurry, improve the inhibitory effect on the volume expansion of other particulate matter during the cycle process, reduce the rebound of the electrode, reduce the expansion force during the cycle of the battery cell, and improve the cycle life of the battery cell.

[0196] In some embodiments, the type of polymerization initiator is not particularly limited, as long as it can play a role in initiating the polymerization reaction. For example, the polymerization initiator may include at least one of potassium sulfate, potassium persulfate, and sodium persulfate.

[0197] In the second mixed solution, the mass percentage of the polymerization initiator is 1% to 3%. For example, the mass percentage of the polymerization initiator can be 1.5%, 2%, 2.5% or within the range of any of the above values. Optionally, the mass percentage of the polymerization aid is 2% to 2.5%. The mass percentage of the polymerization initiator in the second mixed solution is within a suitable range, which is conducive to initiating and promoting the polymerization reaction.

[0198] In some embodiments, the temperature of the second heat treatment is 50° C. to 85° C., and can be 65° C. to 75° C. The temperature of the second heat treatment is controlled within a suitable range, which is beneficial to further promote the polymerization reaction.

[0199] As a non-limiting example of step S20, potassium sulfate can be added to the solution of the pre-reacted mixture, and polyethylene glycol monoacrylate and acrylonitrile are simultaneously and evenly added, and simultaneously heated to 70°C and stirred for 2 to 3 hours; during the reaction, each reagent can be slowly added in equal proportions according to the required mass percentage, and the composite negative electrode material can be obtained after purification by removing the supernatant by centrifugation.

[0200] In some embodiments, before obtaining the composite negative electrode material, the method of the present application may further include the following step S30 of preparing the acrylic polyether polyol monoester:

[0201] S30, contacting acrylic acid with polyether polyol to undergo esterification reaction to obtain the acrylic acid polyether polyol monoester.

[0202] Acrylic acid polyether polyol monoester can be obtained by esterifying acrylic acid with polyether polyol, wherein the ether bonds contained in the acrylic acid polyether polyol monoester can effectively enhance the flexibility of the polymer structure in the composite negative electrode material, thereby enhancing the flexibility of the composite negative electrode material, thereby enhancing the flexibility of the electrode sheet containing the composite negative electrode material and improving the processability of the electrode sheet.

[0203] In some embodiments, the type of the polyether polyol is not particularly limited, as long as it can undergo esterification reaction with acrylic acid and includes an ether bond in the molecular structure. For example, the polyether polyol may include at least one of polyethylene glycol, polypropylene glycol and polytetramethylene glycol.

[0204] In some embodiments, the degree of polymerization of the polyether polyol is 2 to 200, and can be 50 to 150. The degree of polymerization of the polyether polyol is mainly reflected in the length of the side chain. A suitable degree of polymerization can improve the problem of brittleness of the pole piece caused by the linear structure of the main chain, but too long can easily lead to problems such as decreased adhesion and slurry processing.

[0205] In some implementations, the above step S30 may further include the following steps:

[0206] S300, contacting and mixing the acrylic acid and the polyether polyol in water to form a third mixed solution;

[0207] S310, adding a catalyst and an inhibitor to the third mixed liquid;

[0208] S320, performing a third heat treatment on the third mixed solution to obtain a solution of the acrylic polyether polyol monoester;

[0209] S330, purifying the solution of the acrylic acid polyether polyol monoester to obtain the acrylic acid polyether polyol monoester.

[0210] In the above steps S300 to S330, acrylic acid and polyether polyol may undergo esterification reaction under the action of a catalyst and an inhibitor. The esterification reaction may link the carboxyl group in acrylic acid with the hydroxyl group in polyether polyol to form acrylic acid polyether polyol monoester.

[0211] In some embodiments, the molar ratio of acrylic acid to polyether polyol is (5:1) to (1:1), and can be (1.5:1) to (2.5:1). The molar ratio of acrylic acid to polyether polyol is controlled within a suitable range, which is conducive to the occurrence of esterification reaction, thereby obtaining the target product acrylic acid polyether polyol monoester.

[0212] In some embodiments, the type of the catalyst is not particularly limited, as long as it can catalyze the esterification reaction and increase the reaction rate. For example, the catalyst may include at least one of p-toluenesulfonic acid, sulfuric acid and aluminum oxide.

[0213] In some embodiments, in the third mixed solution, the mass percentage of the catalyst is 3% to 10%. For example, the mass percentage of the catalyst can be 4%, 5%, 6%, 7%, 8%, 9% or within the range of any of the above values. Optionally, the mass percentage of the catalyst is 5% to 9%. The mass percentage of the catalyst in the third mixed solution is within a suitable range, which can make the catalyst play a better catalytic promotion effect.

[0214] In some embodiments, the type of the polymerization inhibitor is not particularly limited, as long as it can prevent the polymerization of acrylic acid monomers in the esterification reaction. For example, the polymerization inhibitor may include at least one of hydroquinone, p-hydroxyanisole and 2,6-di-tert-butyl-p-cresol.

[0215] In some embodiments, in the third mixed solution, the mass percentage of the polymerization inhibitor is 1% to 5%. For example, the mass percentage of the polymerization inhibitor can be 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5% or within the range of any of the above values. Optionally, the mass percentage of the polymerization inhibitor is 3% to 4.5%. The mass percentage of the polymerization inhibitor in the third mixed solution is within a suitable range, so that the polymerization inhibitor can better prevent the polymerization of acrylic acid monomers.

[0216] In some embodiments, the temperature of the third heat treatment is 50° C. to 85° C., and may be 65° C. to 75° C. The temperature of the third heat treatment is controlled within a suitable range, which is beneficial to promoting the esterification reaction.

[0217] As a non-limiting example of the esterification reaction in step S30, the reaction process can be represented by any one of the following reaction formulas (I) to (III):

[0218]

[0219] As a non-limiting example of step S30, polyethylene glycol and acrylic acid can be added to distilled water in a molar ratio of 1:1 to obtain a solution with a concentration of 20%; a catalyst and an inhibitor are added, stirred evenly, and heated to 70°C to obtain a solution of polyethylene glycol monoacrylate. The solution of polyethylene glycol monoacrylate is then dissolved in dichloromethane, washed with a 5% sodium hydroxide solvent, separated to remove the aqueous solution, and then washed with a saturated sodium chloride solution, separated to remove excess polyether substances, and finally distilled to remove the solvent to obtain a polyethylene glycol monoacrylate monomer.

[0220] In some embodiments, before obtaining the composite negative electrode material, the method of the present application may further include the following step S40 of preparing the acrylate:

[0221] S40, contacting acrylic acid with an alkaline reagent to react, to obtain the acrylic acid salt.

[0222] Acrylic acid is salified by reacting acrylic acid with an alkaline reagent to obtain acrylate. By salifying the carboxylic acid functional group in acrylic acid, the hydrogen bonding effect on the polyacrylate molecular chain can be reduced during the subsequent polymerization reaction, and the mutual agglomeration between the molecular chains can be weakened, so that the final composite negative electrode material can be evenly dispersed in the slurry, thereby improving the kinetic performance of the battery cell.

[0223] In some implementations, the above step S40 may further include the following steps:

[0224] S400, adding an alkaline agent to the acrylic acid solution to adjust the pH value of the solution to 7-8, thereby obtaining the acrylate solution;

[0225] S410, distilling and drying the acrylate solution.

[0226] In the above steps S400 to S410, the amount of reactants acrylic acid and alkaline reagent can be indirectly controlled by controlling the pH value of the solution. By controlling the amount of the reactants within a suitable range, the salification reaction is facilitated, thereby obtaining the target product acrylate.

[0227] In some embodiments, the type of the acrylate is not particularly limited, as long as the polymerization reaction can be achieved in the subsequent reaction process and the polymer structure of the polyacrylate can be obtained in the organic polymer. For example, the acrylate can include at least one of sodium acrylate, potassium acrylate, lithium acrylate and ammonium acrylate.

[0228] In some embodiments, the type of the alkaline agent is not particularly limited, as long as it can salt the acrylic acid to reduce the carboxyl groups contained in the acrylic acid. For example, the alkaline agent includes at least one of sodium hydroxide, potassium hydroxide, lithium hydroxide and ammonia water.

[0229] As a non-limiting example of the salification reaction in step S40, the reaction process can be represented by the following reaction formula (IV):

[0230]

[0231] As a non-limiting example of step S40, sodium hydroxide solution may be slowly added dropwise to an aqueous solution of acrylic acid, and the solution may be stirred during the adding process until the pH value of the solution reaches 7-8, and then distilled and dried to obtain sodium acrylate particles.

[0232] Negative electrode

[0233] The third aspect of the embodiment of the present application provides a negative electrode sheet, the negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, the negative electrode film layer includes a negative electrode active material, and the negative electrode active material includes the composite negative electrode material of the first aspect of the present application or the composite negative electrode material prepared by the method of the second aspect of the present application. As an example, the negative electrode current collector has two surfaces opposite to each other in its own thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.

[0234] The negative electrode plate includes the composite negative electrode material provided by the manufacturer, wherein the composite negative electrode material can improve the dispersion effect of the slurry, enhance the dispersion uniformity of the slurry, and reduce the occurrence of slurry gelation; after the slurry containing the composite negative electrode is applied to the plate, the cold pressing window of the plate after drying can be improved, and the processing performance of the plate can be improved. At the same time, during the cycle process, the polymer structure in the composite negative electrode material can play a role in inhibiting the volume expansion of the silicon-based material, thereby inhibiting the rebound of the negative electrode plate, reducing the growth of the expansion force of the battery cell, and improving the cycle life of the battery cell.

[0235] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material on a polymer material substrate. Among them, the metal material includes but is not limited to copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc., and the polymer material substrate includes but is not limited to polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE) and other substrates.

[0236] In some embodiments, the negative electrode active material does not exclude other negative electrode active materials other than the composite negative electrode material provided in the present application. Other negative electrode active materials may adopt negative electrode active materials for secondary batteries known in the art. As an example, other negative electrode active materials may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0237] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).

[0238] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0239] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0240] In some embodiments, the negative electrode sheet can be prepared in the following manner: the above-mentioned components for preparing the negative electrode sheet, such as the composite negative electrode material, optional other negative electrode active materials, optional binder, optional conductive agent and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0241] The negative electrode plate of the present application does not exclude other additional functional layers in addition to the negative electrode film layer. For example, in some embodiments, the negative electrode plate of the present application also includes a conductive primer layer (for example, composed of a conductive agent and a binder) sandwiched between the negative electrode current collector and the negative electrode film layer and disposed on the surface of the negative electrode current collector. In some other embodiments, the negative electrode plate of the present application also includes a protective layer covering the surface of the negative electrode film layer.

[0242] Secondary battery

[0243] A fourth aspect of the embodiments of the present application provides a secondary battery, including any device in which an electrochemical reaction occurs to convert chemical energy into electrical energy, for example, a lithium ion secondary battery or a sodium ion secondary battery.

[0244] In some embodiments, the secondary battery of the present application includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte. During the battery charging and discharging process, active ions are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.

[0245] [Negative electrode]

[0246] The negative electrode plate adopts the negative electrode plate provided in the third aspect of the present application.

[0247] [Positive electrode]

[0248] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode film layer includes a positive electrode active material. As an example, the positive electrode current collector has two surfaces opposite to each other in its own thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.

[0249] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material on a polymer material substrate. Among them, the metal material includes but is not limited to aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc. Polymer material substrate (such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0250] In some embodiments, the positive electrode active material may include a positive electrode active material for a battery that is well known in the art. As an example, the positive electrode active material may include at least one of the following materials: a lithium-containing phosphate with an olivine structure, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05O2) and its modified compounds, etc. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.

[0251] In some embodiments, the positive electrode active material may also include at least one of the following materials: sodium transition metal oxide, polyanionic compound and Prussian blue compound. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more.

[0252] As an optional technical solution of the present application, in the sodium transition metal oxide, the transition metal may be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce. The sodium transition metal oxide is, for example, Na x MO2, wherein M is one or more of Ti, V, Mn, Co, Ni, Fe, Cr and Cu, and 0<x≤1.

[0253] As an optional technical solution of the present application, the polyanionic compound can be a compound having sodium ions, transition metal ions and tetrahedral (YO4) n- A class of compounds with anionic units. The transition metal can be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce; Y can be at least one of P, S and Si; n represents (YO4) n- valence state.

[0254] Polyanionic compounds can also be those with sodium ions, transition metal ions, tetrahedral (YO4) n- A class of compounds containing anion units and halogen anions. The transition metal can be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce; Y can be at least one of P, S and Si, and n represents (YO4) n- valence state; the halogen may be at least one of F, Cl and Br.

[0255] Polyanionic compounds can also be sodium ions, tetrahedral (YO4) n- Anion unit, polyhedral unit (ZO y ) m+ and an optional halogen anion. Y can be at least one of P, S and Si, and n represents (YO4) n-valence state; Z represents a transition metal, which may be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce; m represents (ZO y ) m+ valence state; the halogen may be at least one of F, Cl and Br.

[0256] Polyanionic compounds include NaFePO4, Na3V2(PO4)3 (sodium vanadium phosphate, abbreviated as NVP), Na4Fe3(PO4)2(P2O7), NaM'PO4F (M' is one or more of V, Fe, Mn and Ni) and Na3(VOy)2(PO4)2F 3-2y At least one of (0≤y≤1).

[0257] Prussian blue compounds can be sodium ions, transition metal ions and cyanide ions (CN - ). The transition metal may be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce. Prussian blue compounds are, for example, Na a Me b Me' c (CN)6, wherein Me and Me' are each independently at least one of Ni, Cu, Fe, Mn, Co and Zn, 0<a≤2, 0<b<1, 0<c<1.

[0258] In some embodiments, the positive electrode film layer may further include a conductive agent, for example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0259] In some embodiments, the positive electrode film layer may also optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0260] The positive electrode sheet in the present application can be prepared according to conventional methods in the art. For example, the positive electrode film layer is usually formed by coating the positive electrode slurry on the positive electrode current collector, drying and cold pressing. The positive electrode slurry is usually formed by dispersing the positive electrode active material, optional binder, optional conductive agent and any other components in a solvent and stirring them evenly. The solvent can be N-methylpyrrolidone (NMP), but is not limited thereto.

[0261] The positive electrode sheet of the present application does not exclude other additional functional layers in addition to the positive electrode film layer. For example, in some embodiments, the positive electrode sheet of the present application also includes a conductive primer layer (for example, composed of a conductive agent and a binder) sandwiched between the positive electrode collector and the positive electrode film layer and disposed on the surface of the positive electrode collector. In other embodiments, the positive electrode sheet of the present application also includes a protective layer covering the surface of the positive electrode film layer.

[0262] [Electrolyte]

[0263] The electrolyte plays a role in conducting active ions between the positive electrode plate and the negative electrode plate. The electrolyte that can be used in the secondary battery of the present application can be an electrolyte known in the prior art.

[0264] In some embodiments, the electrolyte includes an organic solvent, an electrolyte salt, and optional additives. The types of the organic solvent, the electrolyte salt, and the additives are not particularly limited and can be selected according to requirements.

[0265] In some embodiments, the electrolyte salt can be selected from one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalatophosphate) (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).

[0266] In some embodiments, the electrolyte salt may include but is not limited to at least one of NaPF6, NaClO4, NaBCl4, NaSO3CF3 and Na(CH3)C6H4SO3. The above electrolyte salts may be used alone or in combination of two or more.

[0267] In some embodiments, as an example, the organic solvent includes but is not limited to ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), cyclopentane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS) and diethyl sulfone (ESE) At least one. The above organic solvents can be used alone or in combination. Alternatively, two or more of the above organic solvents are used in combination.

[0268] In some embodiments, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and may also include additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.

[0269] As an example, the additive includes but is not limited to at least one of fluoroethylene carbonate (FEC), vinylene carbonate (VC), vinyl carbonate (VEC), diethylene sulfate (DTD), propylene sulfate, vinyl sulfite (ES), 1,3-propane sultone (PS), 1,3-propylene sultone (PST), sulfonate cyclic quaternary ammonium salt, succinic anhydride, succinonitrile (SN), adiponitrile (AND), tris(trimethylsilyl) phosphate (TMSP), and tris(trimethylsilyl) borate (TMSB).

[0270] The electrolyte can be prepared according to conventional methods in the art. For example, an organic solvent, an electrolyte salt, and an optional additive can be mixed uniformly to obtain an electrolyte. There is no particular restriction on the order of adding the materials. For example, the electrolyte salt and the optional additive are added to the organic solvent and mixed uniformly to obtain the electrolyte; or, the electrolyte salt is first added to the organic solvent, and then the optional additive is added to the organic solvent and mixed uniformly to obtain the electrolyte.

[0271] [Isolation film]

[0272] The separator is disposed between the positive electrode and the negative electrode, and mainly plays the role of preventing the positive and negative electrodes from short-circuiting, while allowing active ions to pass through. The present application has no particular restrictions on the type of separator, and any known porous structure separator with good chemical stability and mechanical stability can be selected.

[0273] In some embodiments, the material of the isolation membrane can be selected from one or more of glass fiber, non-woven fabric, polyethylene, polypropylene, and polyvinylidene fluoride, but is not limited to these. The isolation membrane can be a single-layer film or a multi-layer composite film. When the isolation membrane is a multi-layer composite film, the materials of each layer are the same or different. In some embodiments, a ceramic coating or a metal oxide coating can also be provided on the isolation membrane.

[0274] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.

[0275] In some embodiments, the secondary battery cell may include an outer package that can be used to encapsulate the electrode assembly and the electrolyte.

[0276] In some embodiments, the outer packaging of the secondary battery cell may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery cell may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT), polybutylene succinate (PBS), etc.

[0277] The present application has no particular restrictions on the shape of the secondary battery cell, which can be cylindrical, square or any other shape. Figure 1 The secondary battery 5 is a square structure as an example.

[0278] In some embodiments, reference Figure 2 , the outer package may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate are enclosed to form a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 is used to cover the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, which can be adjusted according to needs.

[0279] In some embodiments, the secondary battery may also be a battery module composed of a plurality of battery cells. The battery module may contain a plurality of secondary battery cells, and the specific number may be adjusted according to the application and capacity of the battery module.

[0280] Figure 3 4 is an example of a battery module. Figure 3In the battery module 4, the plurality of secondary battery cells 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary battery cells 5 may be fixed by fasteners.

[0281] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary battery cells 5 are received in the receiving space.

[0282] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.

[0283] In some embodiments, the battery cells mentioned above may also be directly assembled into a battery pack, and the number of battery cells contained in the battery pack may be adjusted according to the application and capacity of the battery pack.

[0284] Figure 4 and Figure 5 1 is a battery pack 1 as an example. Figure 4 and Figure 5 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3, wherein the upper box body 2 is used to cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 may be arranged in the battery box in any manner.

[0285] Electrical equipment

[0286] The fifth aspect of the embodiment of the present application provides an electrical device, the device includes at least one of the secondary battery, battery module, or battery pack of the present application. The secondary battery, battery module or battery pack can be used as a power source for the device, and can also be used as an energy storage unit for the device. The device may be, but is not limited to, a mobile device, an electric vehicle, an electric train, a ship and a satellite, an energy storage system, etc. For example, it can be a laptop computer, a pen-input computer, a mobile computer, an e-book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini CD, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery, etc.

[0287] The device can select a secondary battery, a battery module or a battery pack according to its usage requirements.

[0288] Figure 6The device is used as an example. The device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the device's requirements for high power and high energy density, a battery pack or a battery module can be used.

[0289] Example

[0290] The following examples describe the disclosure of the present invention in more detail, and these examples are intended for illustrative purposes only, as various modifications and variations within the scope of the disclosure of the present invention are apparent to those skilled in the art. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are by mass, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.

[0291] Example 1

[0292] Preparation of composite negative electrode materials

[0293] (1) Slowly drop a sodium hydroxide solution (10% by mass) into an acrylic acid aqueous solution (15% by mass), stirring the solution during the dropwise addition until the pH value of the solution is 7.5, and then distilling and drying to obtain sodium acrylate particles.

[0294] (2) Polyethylene glycol and acrylic acid are added to distilled water in a molar ratio of 2:1 to prepare a 20% solution, 5% by weight of toluenesulfonic acid and 3% by weight of hydroquinone are added, the mixture is stirred evenly and heated to 70° C. to obtain an aqueous solution of polyethylene glycol monoacrylate.

[0295] (3) The product of (2) is dissolved in dichloromethane, washed with a 5% by weight sodium hydroxide solvent, separated to remove the aqueous solution, then washed with a saturated sodium chloride solution, separated to remove excess polyether substances, and finally distilled to remove the solvent to obtain acrylic acid polyethylene glycol monoester.

[0296] (4) Sodium dodecyl sulfate and acrylic acid and the sodium acrylate in (1) are added to distilled water in a ratio of 3%, 20% and 10% by weight to obtain an aqueous solution, hydroxylated CNT (5% by weight) and silicon powder (50% by weight) are added to the solution, the mixture is stirred evenly and heated to 70°C.

[0297] (5) Add 2% by weight of potassium sulfate to (4), and simultaneously and evenly add the acrylic acid polyethylene glycol monoester (30% by weight) and acrylonitrile (15% by weight) prepared in (3), and simultaneously heat to 70° C. and continue stirring for 2 to 3 hours; during the reaction, reagents can be slowly added in equal proportions, and the target product composite negative electrode material is obtained by removing the supernatant by centrifugal washing.

[0298] Preparation of negative electrode

[0299] The active material graphite, composite negative electrode material, conductive agent acetylene black, thickener sodium carboxymethyl cellulose (CMC), and binder (SBR) are dissolved in solvent deionized water at a weight ratio of 90:5:1:2:1, and then evenly mixed with deionized water to prepare a negative electrode slurry. The slurry is coated on copper foil, dried, and then cold-pressed and cut to obtain a negative electrode sheet.

[0300] Preparation of positive electrode

[0301] The positive electrode active material NCM, the conductive agent acetylene black, and the binder polyvinylidene fluoride (PVDF) are dissolved in the solvent N-methylpyrrolidone (NMP) in a weight ratio of 96.5:1.5:2, and the positive electrode slurry is obtained after being fully stirred and mixed; the positive electrode slurry is then evenly coated on the positive electrode collector, and then dried, cold pressed, and cut to obtain the positive electrode sheet.

[0302] Preparation of electrolyte

[0303] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent; LiPF6 is dissolved in the above organic solvent, and fluoroethylene carbonate (FEC) is added and mixed evenly to obtain an electrolyte; wherein the concentration of LiPF6 is 1 mol / L.

[0304] Preparation of isolation membrane

[0305] PE porous film is used as the isolation membrane.

[0306] Preparation of lithium-ion batteries

[0307] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare cell, the tabs are welded to the bare cell, and the bare cell is placed in an aluminum shell, and baked at 80°C to remove water, and then the electrolyte is injected and sealed to obtain an uncharged battery. The uncharged battery then goes through the processes of static, hot and cold pressing, formation, shaping, and capacity testing in sequence to obtain a lithium-ion battery.

[0308] Examples 2 to 25

[0309] The preparation method of the lithium ion battery is similar to that of Example 1, except that the composite negative electrode material and the related parameters in the preparation process are adjusted, and the specific parameters are shown in the following Table 1. Wherein, " / " indicates that the corresponding parameter does not exist.

[0310] Comparative Example 1

[0311] The negative electrode sheet of Comparative Example 1 does not contain a composite negative electrode material.

[0312] Comparative Example 2

[0313] In the negative electrode sheet of Comparative Example 2, silicon powder is used instead of the composite negative electrode material.

[0314] Comparative Example 3

[0315] In the negative electrode sheet of Comparative Example 3, the conductive agent acetylene black is used instead of the composite negative electrode material.

[0316] Comparative Example 4

[0317] In the negative electrode sheet of Comparative Example 4, the binder SBR is used instead of the composite negative electrode material.

[0318] Comparative Example 5

[0319] The method for preparing the composite negative electrode material in Comparative Example 5 is similar to that in Example 1, except that no silicon powder is added during the preparation process.

[0320] Comparative Example 6

[0321] The method for preparing the composite negative electrode material in Comparative Example 6 is similar to that in Example 1, except that no hydroxylated carbon nanotubes are added during the preparation process.

[0322] Comparative Example 7

[0323] The method for preparing the composite negative electrode material in Comparative Example 7 is similar to that in Example 1, except that: an excess of silicon powder is used during the preparation process.

[0324] Comparative Example 8

[0325] The method for preparing the composite negative electrode material in Comparative Example 8 is similar to that in Example 1, except that an excess of hydroxylated carbon nanotubes is used during the preparation process.

[0326] Test Section

[0327] (1) Test of the processability of slurry and pole piece

[0328] Stability test of slurry: take an appropriate amount of stirred slurry in a beaker, seal it with plastic wrap, and check the sedimentation / gelation of the slurry after standing for 24 hours: open the plastic wrap, gently move the surface of the slurry with a steel ruler to check whether there is any abnormality on the surface of the slurry; slowly extend the steel ruler vertically along the edge of the beaker to the bottom of the beaker, scrape the slurry at the bottom and then pull out the steel ruler to check the precipitation brought out by the steel ruler.

[0329] Adhesion test of the electrode: Take the electrode to be tested, cut a sample with a suitable length and width with a blade, and stick the special double-sided tape on the steel plate. The width of the tape must be fixed. Stick the cut electrode sample on the double-sided tape with the test surface facing down, compact it with a roller, and use a tensile tester to test the force corresponding to the maximum peel strength, and convert it to N / m according to the width of the tape.

[0330] Toughness of pole piece: Take an appropriate amount of cold-pressed pole piece sample, fold the sample in half along the TD direction, place it on the flat surface of the test bench, roll it once with a 2kg cylindrical roller, and then fold it again once to check whether there is light transmittance or breakage at the crease. If so, it is NG. If not, repeat the above test, check the light transmittance once, add 1 to the toughness, and record the maximum number of non-NG toughness.

[0331] (2) Lithium-ion battery energy density and cycle life test

[0332] The cycle test temperature is 25°C. The battery is charged to the upper limit voltage at a constant current of 0.33C, charged to 0.05C at a constant voltage, and discharged to the lower limit voltage at 0.33C after standing for 5 minutes. The capacity obtained in this step is the initial capacity. The capacity is multiplied by the average discharge voltage and then divided by the cell volume to obtain the energy density. A 0.33C charge / 0.33C discharge cycle test is performed until the capacity decays to 80% SOH, and the corresponding number of cycles is recorded to obtain the corresponding life data.

[0333] (3) Battery cell expansion force test

[0334] Before the test (2), the battery cell is fixed in the fixture of the pressure sensor and clamped with a fixed pressure. The capacity calibration and cycle test are carried out according to the process in (2). The expansion force change is monitored during the cycle. The ratio of the expansion force increment when the capacity decays to 80% to the initial expansion force is the expansion force change.

[0335] (4) Lithium-ion battery dynamic performance test

[0336] DC resistance DCR test: After charging the battery to the nominal voltage at 0.33C, charge it at constant voltage until the current is ≤0.05C, and record the capacity as 100% SOC; leave it for 5 minutes. Discharge the battery to 50% SOC at a constant current rate of 0.33C, and after the adjustment is completed, test the voltage of the lithium-ion battery and record it as V1; discharge it at a constant current rate of 4C (recorded as: I) for 10s, and after the discharge, test the voltage of the lithium-ion battery and record it as V2; use the formula to calculate the DC resistance: DCR = (V1-V2) / I.

[0337] Table 2 gives the performance test results of Examples 1 to 24 and Comparative Examples 1 to 8.

[0338] By comparing the examples and comparative examples, it can be seen that the composite negative electrode material obtained by combining silicon-based materials, organic polymers and hydroxylated carbon nanotubes can effectively improve the processability of the pole piece, reduce the expansion force of the battery cell, and improve the energy density, cycle life and kinetic performance of the lithium-ion battery. By controlling the relevant condition parameters in the preparation process of the composite negative electrode material, the various performances of the negative pole piece, battery cell and lithium-ion battery can be adjusted, so that a lithium-ion battery with better comprehensive performance can be obtained according to actual application requirements.

[0339] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0340] The above is only a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any technician familiar with the technical field can easily think of various equivalent modifications or replacements within the technical scope disclosed in the present application, and these modifications or replacements should be included in the protection scope of the present application. Therefore, the protection scope of the present application shall be based on the protection scope of the claims, and the description and drawings can be used to interpret the protection scope of the claims.

[0341] Table 1

[0342]

[0343]

[0344] Table 2

[0345]

Claims

1. A composite negative electrode material, characterized in that: include: Silicon-based material matrix; and A polymer structure coated and connected to at least a portion of the surface of the silicon-based material substrate, wherein the polymer structure comprises an organic polymer and hydroxylated carbon nanotubes, at least a portion of the organic polymer is combined with the hydroxylated carbon nanotubes to form a composite, and the organic polymer comprises a compound having a structure shown in formula (1), (1) In formula (1), m is an integer of 2500 to 20000, and R1 is a polymer unit containing an ester group and a nitrile group.

2. The composite negative electrode material according to claim 1, characterized in that The polymer unit includes a polymer unit of the structural formula shown in formula (2), (2) In formula (2), ** represents the connection site of the polymer unit, p is an integer from 1000 to 5000, q is an integer from 1000 to 15000, f is an integer from 500 to 4000, 2≤n≤200, and each R2 is independently selected from , and One of the following, * indicates the connection site of R2, M + Selected from Na + , K + , Li + and NH4 + One of them.

3. The composite negative electrode material according to claim 1, characterized in that: The polymeric structure is connected to at least a portion of the surface of the silicon-based material matrix through ester groups and / or hydrogen bonds.

4. The composite negative electrode material according to claim 3, characterized in that: The polymeric structure is connected to at least a portion of the surface of the silicon-based material matrix through an ester group.

5. The composite negative electrode material according to any one of claims 1 to 4, characterized in that: The composite negative electrode material satisfies at least one of the following conditions: (1) The silicon-based material matrix contains hydroxyl functional groups and / or carboxyl functional groups; and (2) The organic polymer in the composite is combined with the hydroxylated carbon nanotubes via ester groups and / or hydrogen bonds; (3) The surface of the hydroxylated carbon nanotube is connected with at least one hydroxyl group.

6. The composite negative electrode material according to claim 5, characterized in that: The organic polymer in the composite is bonded to the hydroxylated carbon nanotubes via an ester group.

7. The composite negative electrode material according to any one of claims 1 to 4, characterized in that: The composite negative electrode material satisfies at least one of the following conditions: (1) The silicon-based material includes at least one of elemental silicon, silicon-oxygen compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys; and (2) The hydroxylated carbon nanotubes include hydroxylated single-walled carbon nanotubes and / or hydroxylated multi-walled carbon nanotubes.

8. The composite negative electrode material according to any one of claims 1 to 4, characterized in that: The composite negative electrode material satisfies at least one of the following conditions: (1) In the composite negative electrode material, the mass percentage of the silicon-based material matrix is ​​15% to 90%; (2) In the composite negative electrode material, the mass percentage of the organic polymer is 6% to 60%; (3) In the composite negative electrode material, the mass percentage of the composite is 10% to 80%.

9. The composite negative electrode material according to claim 8, characterized in that: The composite negative electrode material satisfies at least one of the following conditions: (1) In the composite negative electrode material, the mass percentage of the silicon-based material matrix is ​​40% to 85%; (2) In the composite negative electrode material, the mass percentage of the organic polymer is 15% to 25%; (3) In the composite negative electrode material, the mass percentage of the composite is 20% to 50%.

10. A method for preparing a composite negative electrode material, characterized in that: include: reacting acrylate with acrylic acid, hydroxylated carbon nanotubes, and a silicon-based material matrix to obtain a pre-reacted mixture; and The pre-reacted mixture is polymerized with acrylonitrile and acrylic acid polyether polyol monoester to form a polymer structure coated on at least part of the surface of the silicon-based material matrix to obtain a composite negative electrode material, wherein the composite negative electrode material comprises the silicon-based material matrix and the polymer structure, the polymer structure comprises an organic polymer and the hydroxylated carbon nanotubes, at least part of the organic polymer is combined with the hydroxylated carbon nanotubes to form a composite, and the organic polymer comprises a compound having a structure shown in formula (1). (1) In formula (1), m is an integer of 2500 to 20000, and R1 is a polymer unit containing an ester group and a nitrile group.

11. The method according to claim 10, characterized in that The step of reacting acrylate with acrylic acid, hydroxylated carbon nanotubes, and a silicon-based material matrix comprises: Under the action of a polymerization aid, the acrylate, the acrylic acid, the hydroxylated carbon nanotubes and the silicon-based material matrix are contacted and reacted.

12. The method according to claim 11, characterized in that The method satisfies at least one of the following conditions: (1) The acrylate includes at least one of sodium acrylate, potassium acrylate, lithium acrylate and ammonium acrylate; (2) The polymerization aid includes sodium dodecyl sulfonate and / or sodium dodecyl sulfate; (3) The silicon-based material includes at least one of elemental silicon, silicon-oxygen compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys; and (4) The hydroxylated carbon nanotubes include hydroxylated single-walled carbon nanotubes and / or hydroxylated multi-walled carbon nanotubes.

13. The method according to claim 11 or 12, characterized in that The step of making the acrylate, the acrylic acid, the hydroxylated carbon nanotubes and the silicon-based material matrix contact and react under the action of a polymerization aid comprises: The polymerization aid, the acrylate, the acrylic acid, the hydroxylated carbon nanotubes and the silicon-based material matrix are contacted and mixed in water to form a first mixed solution; and The first mixed liquid is subjected to a first heat treatment so as to cause a prepolymerization reaction between the acrylate, the acrylic acid, the hydroxylated carbon nanotubes and the silicon-based material matrix.

14. The method according to claim 13, characterized in that The method satisfies at least one of the following conditions: (1) In the first mixed solution, the mass percentage of the acrylate is 3% to 25%; (2) In the first mixed solution, the mass percentage of the acrylic acid is 5% to 40%; (3) In the first mixed solution, the mass percentage of the hydroxylated carbon nanotubes is 1% to 10%; (4) In the first mixed solution, the mass percentage of the polymerization aid is 2% to 5%; (5) In the first mixed solution, the mass percentage of the silicon-based material matrix is ​​10% to 80%; and (6) The temperature of the first heat treatment is 50°C to 85°C.

15. The method according to claim 14, characterized in that The method satisfies at least one of the following conditions: (1) In the first mixed solution, the mass percentage of the acrylate is 5% to 15%; (2) In the first mixed solution, the mass percentage of the acrylic acid is 15% to 25%; (3) In the first mixed solution, the mass percentage of the hydroxylated carbon nanotubes is 3% to 7%; (4) In the first mixed solution, the mass percentage of the polymerization aid is 3% to 4.5%; (5) The temperature of the first heat treatment is 65° C. to 75° C.

16. The method according to any one of claims 10 to 12, characterized in that: The method of polymerizing the pre-reacted mixture with acrylonitrile and acrylic acid polyether polyol monoester comprises: Under the action of a polymerization initiator, the pre-reacted mixture is brought into contact with the acrylonitrile and the acrylic polyether polyol monoester and polymerized to form the polymerization unit, wherein the polymerization unit includes a polymerization unit of the structural formula shown in formula (2), (2) In formula (2), ** represents the connection site of the polymer unit, p is an integer from 1000 to 5000, q is an integer from 1000 to 15000, f is an integer from 500 to 4000, 2≤n≤200, and each R2 is independently selected from , and One of the following, * indicates the connection site of R2, M + Selected from Na + , K + , Li + and NH4 + One of them.

17. The method according to claim 16, characterized in that The method satisfies at least one of the following conditions: (1) the acrylic polyether polyol monoester comprises at least one of polyethylene glycol acrylate monoester, polypropylene glycol acrylate monoester and polytetramethylene glycol acrylate monoester; and (2) The polymerization initiator includes at least one of potassium sulfate, potassium persulfate and sodium persulfate.

18. The method according to claim 16, characterized in that The method of bringing the pre-reacted mixture into contact with the acrylonitrile and the acrylic polyether polyol monoester and polymerizing the mixture under the action of a polymerization initiator comprises: contacting and mixing the polymerization initiator, the acrylonitrile and the acrylic polyether polyol monoester in the solution of the pre-reacted mixture to obtain a second mixed solution; and The second mixed liquid is subjected to a second heat treatment to allow the acrylonitrile, the acrylic polyether polyol monoester and the pre-reacted mixture to undergo a polymerization reaction.

19. The method according to claim 18, characterized in that The method satisfies at least one of the following conditions: (1) In the second mixed solution, the mass percentage of the polymerization initiator is 1% to 3%; (2) In the second mixed liquid, the mass percentage of acrylonitrile is 5% to 30%; (3) In the second mixed solution, the mass percentage of the acrylic polyether polyol monoester is 10% to 40%; and (4) The temperature of the second heat treatment is 50°C to 85°C.

20. The method according to claim 19, characterized in that The method satisfies at least one of the following conditions: (1) In the second mixed solution, the mass percentage of the polymerization initiator is 2% to 2.5%; (2) In the second mixed liquid, the mass percentage of acrylonitrile is 10% to 20%; (3) In the second mixed solution, the mass percentage of the acrylic polyether polyol monoester is 20% to 35%; and (4) The temperature of the second heat treatment is 65°C to 75°C.

21. The method according to any one of claims 10 to 12, characterized in that: The step of preparing the acrylic polyether polyol monoester is also included: Acrylic acid is contacted with polyether polyol to undergo an esterification reaction, thereby obtaining the acrylic acid polyether polyol monoester.

22. The method according to claim 21, characterized in that The method satisfies at least one of the following conditions: (1) the polyether polyol comprises at least one of polyethylene glycol, polypropylene glycol and polytetramethylene glycol; and (2) The degree of polymerization of the polyether polyol is 2 to 200.

23. The method according to claim 22, characterized in that The polymerization degree of the polyether polyol is 50-150.

24. The method according to claim 21, characterized in that The method of contacting acrylic acid with polyether polyol and causing esterification reaction comprises: contacting and mixing the acrylic acid and the polyether polyol in water to form a third mixed solution; and The third mixed liquid is subjected to a third heat treatment to obtain a solution of the acrylic polyether polyol monoester.

25. The method according to claim 24, characterized in that The method satisfies at least one of the following conditions: (1) the molar ratio of the acrylic acid to the polyether polyol is (5:1) to (1:1); and (2) The temperature of the third heat treatment is 50°C to 85°C.

26. The method according to claim 25, characterized in that The method satisfies at least one of the following conditions: (1) the molar ratio of the acrylic acid to the polyether polyol is (1.5:1) to (2.5:1); and (2) The temperature of the third heat treatment is 65°C to 75°C.

27. The method according to claim 24, characterized in that Before the third mixed liquid is subjected to the third heat treatment, the method further comprises: A catalyst and a polymerization inhibitor are added to the third mixed liquid.

28. The method according to claim 27, characterized in that Satisfy at least one of the following conditions: (1) the catalyst comprises at least one of p-toluenesulfonic acid, sulfuric acid and aluminum oxide; and (2) The polymerization inhibitor includes at least one of hydroquinone, p-hydroxyanisole and 2,6-di-tert-butyl-p-cresol.

29. The method according to claim 27, characterized in that The method satisfies at least one of the following conditions: (1) In the third mixed solution, the mass percentage of the catalyst is 3% to 10%; and (2) In the third mixed solution, the mass percentage of the polymerization inhibitor is 1% to 5%.

30. The method according to claim 29, characterized in that The method satisfies at least one of the following conditions: (1) In the third mixed solution, the mass percentage of the catalyst is 5% to 9%; and (2) In the third mixed liquid, the mass percentage of the inhibitor is 3% to 4.5%.

31. The method according to claim 24, characterized in that After the third mixed liquid is subjected to the third heat treatment, the method further comprises: The acrylic acid polyether polyol monoester solution is purified to obtain the acrylic acid polyether polyol monoester.

32. The method according to any one of claims 10 to 12, characterized in that: The step of preparing the acrylate is also included: Acrylic acid is contacted with an alkaline agent to react to obtain the acrylic acid salt.

33. The method according to claim 32, characterized in that The step of making acrylic acid contact with an alkaline reagent for reaction comprises: Adding an alkaline agent to a solution of acrylic acid to adjust the pH value of the solution to 7-8, thereby obtaining a solution of the acrylate; and The acrylate solution is subjected to distillation and drying treatment.

34. The method according to claim 32, characterized in that The method satisfies at least one of the following conditions: (1) the alkaline reagent comprises at least one of sodium hydroxide, potassium hydroxide, lithium hydroxide and ammonia water; and (2) The acrylate salt includes at least one of sodium acrylate, potassium acrylate, lithium acrylate and ammonium acrylate.

35. A negative electrode plate, comprising the composite negative electrode material according to any one of claims 1 to 9 or the composite negative electrode material prepared by the method according to any one of claims 10 to 34.

36. A secondary battery comprising the negative electrode sheet according to claim 35.

37. An electrical device comprising the secondary battery according to claim 36.

Citation Information

Patent Citations

  • Three-dimensional mixed conductive adhesive used for lithium battery, and battery containing adhesive

    CN109461937A

  • Binder, negative pole piece and electrochemical device

    CN110233235A